The Effects of The Oxytocin Hormone Induction on The Value of The Composition of Etawah Crossbred Goat Milk - Resthu, Muhammad; Araby, Dzarnisa; Wahyuni, Sri (ANIMAL PRODUCTION, 2019)
This study aims to see the extent of influence of oxytocin hormone induction on the nutritional composition of milk in the Etawah CrossbredÂ  goat. This research was conducted in December 2018 in Syiah Kuala District, Banda Aceh, Indonesia. The examined parameters were the levels of fat, nonfat dry matter (BKTL), protein content, lactose content and milk density. The research used 18 Etawah goats and oxytocin hormone. A statistical unpaired t test indicated a highly significant influence (P <0.01) on the increase of milk fat injected with oxytocin hormone, i.e. 4.86% or 37.2% or higher than that without hormone injection. The milk density results showedÂ  a significant effect (P <0.05) on the decrease in goat milk density (28.81% ) which was lower by 10.65% from that without hormone treatment. The level of nonfat dry matter (BKTL), protein content and lactose content had no effect (P> 0.05) in milk, i.e. 8.39%, 3.91% and 3.76%, respectively. In conclusion, hormone oxytocin injection had a highly significant effect on increasing milk fat levels and significantly affected the decrease in milk density but did not affect the level of nonfat dry matter (BKTL), lactose and protein.